The Effect of subdivision regulations on housing typologies - Ali, Luqman Sabir; Qaradaghi, Amjad Muhammad Ali (Sulaimani Journal for Engineering Sciences, 2023)
City planners and related professionals use various tools to control the built environment and its development. This goal couldn’t be achieved without considering housing typology because housing takes up the largest portion of most cities. Land subdivision is one of these planning tools used to regulate the ownership and size of properties. This paper aims to clarify the role of subdivision regulations that are used in Sulaimany City in forming and changing housing typologies. Malkandi district in Sulaimani City was selected as a case study. Descriptive analysis is used to identify the indications of variables. Graphical and statistical analyses have been used to determine the role of subdivision regulations on changing housing typology. According to the findings, the study area has seen two different subdivision systems: Traditional and modern subdivision regulations. The study discovered that changing subdivision regulations play a significant role in changing housing typologies. The Traditional subdivision system encourages organic, irregular blocks with various shapes and sizes. Modern subdivision system leads to raw houses with similar dimensions.
Keywords: Housing typology; subdivision; building regulations; urban regulations; land subdivision